Forgotten intellectual property lore : creativity, entrepreneurship and intellectual property - Ghosh, Shubha, 1964- (Elgar law and entrepreneurship, 2020)
"This innovative book explores forgotten disputes over intellectual property and the ways in which authors, inventors, publishers, courts, and sovereigns have managed these disputes throughout the centuries. With an eye on reform, it chronicles the resilience of legal rules and challenges the methodology behind traditional legal analyses. Disentangling lore from traditions, expert contributors incorporate contextual understandings that are rooted in history, sociology, political science, and literary studies into their analyses. They explore the context of particular cases to reveal the ramifications of specific doctrines for the evolution of intellectual property practices. Chapters illuminate the various facets of intellectual property lore: contract, authorship, common law, and wartime property. Utilising novel methods and previously unpublished materials on copyright, patent, and trademark law, the book examines legal history and developments from multiple perspectives. This rich and accessible book will prove to be a valuable resource for students, academics of intellectual property law, and legal historians. Its use of new materials and exploration of key cases will also be beneficial for intellectual property legal practitioners"--